Ammonia production from water and nitrogen gas using simple dielectric barrier discharge plasma reactor - Novita Wiwoho; Doonyapong Wongsawaeng; Grittima Kongprawes; Phannee Saengkaew; Deni Swantomo (Scientific Reports)
Abstract Ammonia is an important chemical that is primarily used as fertilizer in agriculture. In a simple plasma reactor with water and nitrogen gas as the feed, the synthesis of ammonia was observed to have better reaction conditions than the Haber–Bosch process. The needle-to-plate type of the DBD plasma reactor was built from a borosilicate glass container with a single needle electrode covered by a quartz tube. In this study, the highest concentration of ammonia, measuring 19.7 ppm, was achieved at the reaction condition of 1.4 L/min N2 flow rate, 75 W input power, 1 cm electrode gap size, and 30 min reaction time. The water type was DI water, with a pH value of 5. The UV light addition did not increase ammonia production as it promoted ammonia decomposition instead of formation. The constructed DBD plasma can be used for ammonia production. It is a simple and environmentally friendly process because it requires low input energy and can be operated at ambient conditions.